2012
DOI: 10.1007/s10886-012-0071-4
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Plant Defensive Traits Among Populations in Two Eucalyptus Species Under Elevated Carbon Dioxide

Abstract: Plant secondary metabolites (PSMs) mediate a wide range of ecological interactions. Investigating the effect of environment on PSM production is important for our understanding of how plants will adapt to large scale environmental change, and the extended effects on communities and ecosystems. We explored the production of PSMs under elevated atmospheric carbon dioxide ([CO(2)]) in the species rich, ecologically and commercially important genus Eucalyptus. Seedlings from multiple Eucalyptus globulus and E. pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Eucalyptus species are rich in carbon-based secondary defence compounds, such as phenolics (Moore et al 2004), that are expected to increase at C E (Coley et al 2002), including in fully expanded E. tereticornis leaves (Lawler et al 1997). Contrary to this expectation, however, TP in flush leaves either decreased (E. tereticornis) or showed no response to C E (E. robusta); the absence of a C E effect on TP seen in E. robusta was also in accordance with another study on fully expanded leaves of Eucalyptus globulus (McKiernan et al 2012). In a recent review on the effects of plant secondary compounds at C E , it was observed that there was an increase in phenolic compounds in approximately 50 % of studies, while 7 % of studies showed a decrease and the remaining showed no effect (Ryan et al 2010).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Eucalyptus species are rich in carbon-based secondary defence compounds, such as phenolics (Moore et al 2004), that are expected to increase at C E (Coley et al 2002), including in fully expanded E. tereticornis leaves (Lawler et al 1997). Contrary to this expectation, however, TP in flush leaves either decreased (E. tereticornis) or showed no response to C E (E. robusta); the absence of a C E effect on TP seen in E. robusta was also in accordance with another study on fully expanded leaves of Eucalyptus globulus (McKiernan et al 2012). In a recent review on the effects of plant secondary compounds at C E , it was observed that there was an increase in phenolic compounds in approximately 50 % of studies, while 7 % of studies showed a decrease and the remaining showed no effect (Ryan et al 2010).…”
Section: Discussionsupporting
confidence: 86%
“…The secondary chemistry of Eucalyptus is considerably complex and differs between species (Moore et al 2004;McKiernan et al 2012), and this may impact insect survival. Damage to the midgut of P. atomaria feeding on resistant Eucalyptus grandis clones, ultimately resulting in larval death, has previously been observed and may be a result of secondary metabolites acting synergistically or being converted within the insect to a toxic byproduct (Henery et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For the root dry matter weight, only the treatment with 1,147±216 µmol mol -1 CO 2 had significantly higher values than the other treatments. Otherwise, Novriyanti et al (2012) observed no positive effects of elevated CO 2 concentrations on growth of eucalypts, despite increases on net photosynthetic rate. The increase in plant height and shoot dry weight, as observed in the present study, was also observed by Santos et al (2013) and Ghini et al (2014), in clonal eucalypt plantlets grown under high air-CO 2 concentrations for approximately 60 days.…”
Section: Crescimento De Plantas E Severidade Da Mancha Foliar Em Eucamentioning
confidence: 72%
“…Braga et al (2006) reported a significant increase in phytoalexin production in two soybean cultivars at 720 μmol mol -1 CO 2 , in comparison to an environment with 360 μmol mol -1 . However, McKiernan et al (2012) verified that elevated CO 2 concentration did not affect contents of secondary metabolites, total phenolics, condensed tannins, or the total oil yield of Eucalyptus globulus and Eucalyptus pauciflora.…”
Section: Crescimento De Plantas E Severidade Da Mancha Foliar Em Eucamentioning
confidence: 80%
“…In addition, essential oil also plays a prominent role in plant-plant interplays with an evolutionary origin for communication (Langenheim 1994;Batish et al 2008). While essential oil biosynthesis in plants has genetic determination, environmental conditions also affect its production (McKiernan et al 2012;Sadeghi et al 2014).…”
Section: Discussionmentioning
confidence: 99%